Proceedings of the 19th International Conference on Human-Computer Interaction With Mobile Devices and Services 2017
DOI: 10.1145/3098279.3119836
|View full text |Cite
|
Sign up to set email alerts
|

NatureCHI 2017

Abstract: Being in nature is typically regarded to be calming, relaxing and purifying. When in nature, people often seek to be mobile through physical activity such as hiking. But also, nature provides an opportunity for meditative, mindful or inspiring experiences remote from urban everyday life. Mobile Technologies such as sports tracking technologies, electronic tourist guides, mobile phone integrated cameras and omnipresent social media access, have potential to both enhance and disrupt a user's interaction with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Community building efforts have also been undertaken in this area, such as with NatureCHI [4,5], UbiMount [1], and the CHI Outside SIG at CHI 2017 [7]. But many are still unaware of others working in this area and of the work they are doing.…”
Section: Figures 1 and 2 Highlight Two Important Questions Aboutmentioning
confidence: 99%
“…Community building efforts have also been undertaken in this area, such as with NatureCHI [4,5], UbiMount [1], and the CHI Outside SIG at CHI 2017 [7]. But many are still unaware of others working in this area and of the work they are doing.…”
Section: Figures 1 and 2 Highlight Two Important Questions Aboutmentioning
confidence: 99%
“…Martin, 2017). There is potential here for backpacking apps to be designed in such a way that they encourage users to learn and maintain these important skills, and to focus more on the experience of being in a wilderness area (Häkkilä et al, 2017). One recurring sub-theme centred around anxieties resulting from the lack of availability of reliable power sources when on the trail, and revealed that the issue in backpacking is compounded by the need to use and maintain a number of quite different devices, each with their own battery lives and energy requirements.…”
Section: Discussionmentioning
confidence: 99%
“…The first workshop ran as part of CHI 2016 in San Jose, California and included 11 position papers. The second workshop (Häkkilä et al, 2017) took place alongside MobileHCI 2017 in Vienna, Austria, and included 14 position papers. The workshops comprised both paper presentations (with follow-on discussions) and group activities (see Figure 1).…”
Section: Naturechi Workhop Series: Emerging Themes and Topicsmentioning
confidence: 99%